Improving Fine Motor Skills in Early Childhood Through Origami Playing Activities - Kustini; Prayogo, Basuki Hadi; Sugiarto, Muhammad Agus; Pradana, Pascalian Hadi (Jurnal Smart Paud, 2024)
The aim of this research is to determine the improvement of fine motor skills in young children through origami-playing activities. By playing origami, children's fine motor skills will improve. Paper folding activities will ensure that children use their small muscles to fold the paper that has been provided, so that the small muscles will be sharpened to the maximum. This research uses classroom action research. The data required for this research was collected through observation of the implementation of origami or paper folding activities. During the learning and observation process, the researcher also noted things related to the problem that were in accordance with the researcher's focus. Based on the results of classroom action research (PTK) and data analysis carried out collaboratively between teachers and researchers, it can be concluded that the activity of folding origami paper can improve children's fine motor skills, which can be seen in the increase from cycle I, which obtained a percentage of 55.55% of children. Classical children who were at the minimum criteria for developing according to expectations experienced an increase in cycle II, which obtained a percentage of 94.45% of classical children who were at the minimum criteria for developing according to expectations.